SQL hacks - Cumming, Andrew (Hacks series., 2006)
Whether you're running Access, MySQL, SQL Server, Oracle, or PostgreSQL, this book will help you push the limits of traditional SQL to squeeze data effectively from your database. The book offers 100 hacks -- unique tips and tools -- that bring you the knowledge of experts who apply what they know in the real world to help you take full advantage of the expressive power of SQL. You'll find practical techniques to address complex data manipulation problems. Learn how to: Wrangle data in the most efficient way possible Aggregate and organize your data for meaningful and accurate reporting Make the most of subqueries, joins, and unions Stay on top of the performance of your queries and the server that runs them Avoid common SQL security pitfalls, including the dreaded SQL injection attack Let SQL Hacks serve as your toolbox for digging up and manipulating data. If you love to tinker and optimize, SQL is the perfect technology and SQL Hacks is the must-have book for you.